Spontaneous Late Lens Subluxation Masquerading as Acute Angle Closure Glaucoma - Akram, Imran (Pakistan Journal of Ophthalmology, 2006)
A 45 year old lady was referred to the eye clinic in 1996 by her optician who had noticed a rapid increase in her myopia and was querying keratoconus. She had previously been emmetropic and wore only reading glasses. No signs of keratoconus were seen although it was noted that she had thick crystalline lenses. Intraocular pressures were normal. Pupils were not dilated for ocular examination. There was no iridodonesis. Refraction showed the right eye had a - 2.00 cyl axis 7, while the left eye had a -4.50 cyl axis 90.Keratometry showed minimal astigmatism in either eye and thus the astigmatism was attributed to lenticular changes.With this correction she saw 6/6 in each eye.